The Effectiveness of Contextual Learning Through Discussions and Visits to Cultural Heritage Sites in Improving Cultural Heritage Literacy in High School Students - Kuswono, Kuswono; Utari, Citra Rafika; Salsabilla, Fahra (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
This study aims to assess the effectiveness of contextual learning through workshops and visits to cultural heritage sites in improving cultural heritage literacy in high school students. The method used was a quantitative pre-experimental study with a pretest-posttest design. In addition, observations and supporting interviews were conducted involving 10 students from 10 public and private schools in Metro City. The results showed that contextual learning through workshops and visits to cultural heritage sites significantly improved students' understanding and cultural heritage literacy. This learning approach was effective in increasing historical awareness and student engagement with local culture, and is therefore recommended for integration into history instruction in high school to improve historical literacy. The drawbacks of this learning approach are the lengthy time required and the lack of connection to the school curriculum, particularly regarding out-of-class learning.